Sifat-Sifat Operasi Hitung Perkalian Bilangan Bulat Dalam Pembelajaran Matematika di Sekolah Dasar - Erlangga Kusuma Yuda (Proseding Didaktis: Seminar Nasional Pendidikan Dasar, 2020)
Mathematics is one of the main subjects of education. So that students naturally understand the concept correctly and thoroughly. but, in the learning process there is still a conceptual bias that causes confusion in students. Among them are the material for calculating the multiplication of integers. Based on this, the researcher conducted a study in the form of a literature study on the properties of integer multiplication operations in elementary schools. The method used is literature study with the subject in the form of books, articles, journals and other documents relevant to the research topic. From the results of the study, in general, there are five properties of the operation to calculate the multiplication of integers, namely closed nature, identity characteristics, commutative characteristics, associative characteristics, and distributive characteristics